Southern Sudan Referendum Act 2009 (Tufts Archival Research Center, 2005)
This document is about the Southern Sudan Referendum Act 2009 issued by the Sudanese government. It includes several clauses which, among many, give an interpretation of the terms used, about the established commission and its members, and the regulations and procedures of the referendum.